2016
DOI: 10.1038/aps.2015.121
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of SCT800, a new recombinant FVIII, in hemophilia A mice

Abstract: In hemophilia A mice, SCT800 shows comparable pharmacokinetics and pharmacodynamics to Xyntha at the doses tested, and possibly with better safety properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Moreover, viral removal/inactivation steps (such as nanofiltration) were added to ensure higher safety. Results from preclinical studies, 10 a phase I pharmacokinetic (PK) study, and a phase III on‐demand efficacy‐safety study [unpublished data] have confirmed that SCT800 has PK profiles similar to those of Xyntha ® , and exhibits high in vivo recovery (IVR), effective haemostatic response, good safety and high tolerability. The primary purpose of this study was to evaluate the repeat PKs, efficacy and safety of SCT800 in the prophylaxis and treatment of bleeding episodes in adolescents and adults with severe haemophilia A who have previously received FVIII therapy (NCT03815318).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, viral removal/inactivation steps (such as nanofiltration) were added to ensure higher safety. Results from preclinical studies, 10 a phase I pharmacokinetic (PK) study, and a phase III on‐demand efficacy‐safety study [unpublished data] have confirmed that SCT800 has PK profiles similar to those of Xyntha ® , and exhibits high in vivo recovery (IVR), effective haemostatic response, good safety and high tolerability. The primary purpose of this study was to evaluate the repeat PKs, efficacy and safety of SCT800 in the prophylaxis and treatment of bleeding episodes in adolescents and adults with severe haemophilia A who have previously received FVIII therapy (NCT03815318).…”
Section: Introductionmentioning
confidence: 99%